Efecto del bono de desarrollo humano en la oferta laboral en el Ecuador, año 2018 - Evelyn Aracely Solís Aguirre (2021)
ABSTRACT The objective of this research work is to determine the effect that the Human Development Bonus has on the job offer of heads of poor families in Ecuador in 2018. In addition, it is intended to know the specific characterization of the variables that influence the labor supply of this segment of the population. Based on the assumption that leisure cannot be considered a normal good for the poor population, the multinomial logistic model was applied to determine the probability that heads of families do not work, they work from 1 to 39 hours, they work 40 hours or they work more than 40 hours a week. The structure of this research is divided into chapters: Chapter I presents the problem of the study and the objectives of the work; Chapter II presents the analysis of previous studies and the theoretical basis of the research, addressing concepts and theories related to the aforementioned variables; Chapter III establishes the methodology applied in the research and shows the analysis and discussion of the results obtained. Finally, the conclusions and recommendations of the work are defined. Keywords: poverty, job offer, money transfer, Human Development Bonus. Reviewed by: Mgs. Geovanny Armas Pesántez ENGLISH PROFESSOR C.C. 060277330